Effects of Fermented Citrus Peel on Ameliorating Obesity in Rats Fed with High-Fat Diet - Chung-Hsiung Huang; Shun-Yuan Hsiao; Yung-Hsiang Lin; Guo-Jane Tsai (Molecules, 2022)
Although citrus peel is a waste material, it contains a variety of bioactive components. As our preliminary findings showed that citrus peels fermented with Saccharomyces cerevisiae T1 contained increased levels of anti-obesity flavonoids, the objective of this study was to prepare fermented citrus peel and to investigate its effect on ameliorating obesity in Sprague Dawley (SD) rats fed with a high-fat diet (HFD). After fermentation, the amounts of limonene, nobiletin and 3-methoxynobiletin in citrus peel were markedly increased. SD rats were fed with an HFD for 10 weeks, followed by fermented citrus peel-containing HFD (0.3% or 0.9% w/w) for 6 weeks. Compared with those fed with an HFD alone, lower levels of body weight, visceral fat, body fat percentage, blood triglyceride, total cholesterol, low-density lipoprotein, malondialdehyde and hepatic adipose accumulation were observed in rats fed with fermented citrus peel. In parallel, hepatic levels of acetyl-CoA carboxylase and fatty acid synthase were diminished, and the level of hormone sensitivity lipase in visceral fat was elevated. These results reveal fermented citrus peel is a promising natural product with beneficial effects of alleviating HFD-induced obesity.